Equal matches are only half the story: Why German female graduates earn 27 % less than males - Christina Boll; Julian Sebastian Leppin (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
Germany's occupational and sectoral change towards a knowledge-based economy calls for high returns on education. Nevertheless, female graduates are paid much less than their male counterparts. We find an overall unadjusted gender pay gap among German graduates of 27 %. This corresponds to an approximate wage gap of 32.5 % thereof 20,3 % account for different endowments and 12,2 % for different remunerations of characteristics. Suboptimal job matches of females tied in family and partner contexts are supposed to account for at least part of the gendered wage drift. But overeducation does not matter in this regard. Instead, females earn 4 % less because they work on jobs with fewer years of required education. Furthermore, solely males are granted breadwinner wage premiums and only men successfully avoid wage cuts when reducing working hours. We conclude that the price effect of the gap reflects employers' attributions of gender stereotypes, gendered work attitudes as well as noticeable unobserved heterogeneity within and between sexes.
Keywords: J31; C33; J710; 330